Seems true

Algebra Level 4

True or False?

Let α \alpha , β \beta be complex numbers with non-positive real parts. Then e α e β α β \large |e^{\alpha} - e^{\beta}| \le |\alpha - \beta|

Notation: e 2.718 e \approx 2.718 denotes the Euler's number .

True False

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Alex Burgess
May 2, 2019

Let α = x + i y , β = u + i v \alpha = x+iy, \beta = u+iv with x u = z 0 , y v = θ x-u = z \geq 0, \lvert y - v \rvert = \theta .

e α e β = e x e i y e u e i v = e x e i y e z e i v \lvert e^{\alpha} - e^{\beta} \rvert = \lvert e^x e^{iy} - e^u e^{iv} \rvert = e^x\lvert e^{iy} - e^{-z}e^{iv} \rvert .

Hence,

e α e β = e x 1 e z e i θ = e x ( 1 e z ( cos θ + i sin θ ) = e x ( 1 + e 2 z 2 e z cos θ ) \lvert e^{\alpha} - e^{\beta} \rvert = e^x\lvert 1 - e^{-z}e^{i\theta} \rvert = e^x\lvert (1 - e^{-z}(\cos{\theta} + i\sin{\theta}) \rvert = e^x(1+e^{-2z} -2e^{-z}\cos{\theta} ) .


cos x 1 x 2 2 \cos{x} \geq 1 - \frac{x^2}{2} and 1 e x = x x 2 2 + x 3 6 + . . . x 1-e^{-x} = x-\frac{x^2}{2}+\frac{x^3}{6} + ... \leq x , therefore:

e α e β e x ( 1 e z ) 2 + e y θ 2 z 2 + θ 2 = α β \lvert e^{\alpha} - e^{\beta} \rvert \leq e^x(1-e^{-z})^2 + e^y\theta^2 \leq z^2 + \theta^2 = {\lvert \alpha - \beta \rvert} . []

Hello, Sir. I only understand your solution up to the dividing line, but I noticed that you have a typo. You are missing a square root in that last expression (just before the dividing line). I'm afraid this little blunder might affect the rest of your solution.

James Wilson - 5 months ago

I understand your solution now without the mistakes. You are very smart. Here is what I think it should say without the typos. Let the variables be defined in the same way as you (Alex Burgess) define your variables, except let θ = v y \theta = v-y .

e α e β 2 = e x e i y e u e i v 2 = e 2 x 1 e z e i θ 2 = e 2 x 1 e z ( cos θ + i sin θ ) 2 |e^\alpha-e^\beta|^2 = |e^xe^{iy}-e^ue^{iv}|^2=e^{2x}|1-e^{-z}e^{i\theta}|^2=e^{2x}|1-e^{-z}(\cos{\theta}+i\sin{\theta})|^2

= e 2 x ( 1 + e 2 z 2 e z cos θ ) = e 2 x ( 1 + e 2 z + ( 2 + 2 2 cos θ ) e z ) 1 + e 2 z 2 e z + ( 2 2 cos θ ) e z =e^{2x}(1+e^{-2z}-2e^{-z}\cos{\theta})=e^{2x}(1+e^{-2z}+(-2+2-2\cos{\theta})e^{-z})\leq 1+e^{-2z}-2e^{-z}+(2-2\cos{\theta})e^{-z}

1 + e 2 z 2 e z + θ 2 e z ( 1 e z ) 2 + θ 2 z 2 + θ 2 = α β 2 . \leq 1+e^{-2z}-2e^{-z}+\theta^2e^{-z} \leq (1-e^{-z})^2+\theta^2 \leq z^2 +\theta^2 = |\alpha-\beta|^2.

James Wilson - 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...